Dissipation of Bromide and Metribuzin Affected by Tillage and Crop Residue Management in Subarctic Alaska - Sharratt, Brenton S.; Knight, Charles W. (ARCTIC, 2010)
Prudent use of agricultural fertilizers and herbicides is paramount for sustaining or improving surface and ground water quality in Subarctic regions, but little information is available that documents the loss of chemicals from agricultural lands in the Subarctic. This study aimed to ascertain more clearly how time of application and land management practices affect the loss of bromide and metribuzin in a Subarctic soil. Potassium bromide (KBr), a surrogate for nitrate, and metribuzin, commonly used to control broadleaf weeds, were applied in the autumn of 1996 and the spring of 1997 to a silt loam that had been subjected to conventional tillage (CT), minimum tillage (disk once [DO]), and no tillage (NT) since 1983. Superimposed on the tillage treatments were the removal or retention of barley (Hordeum vulgare L.) stubble and loose straw. Loss of these chemicals was ascertained by sampling the soil profile at the time of heading of barley, before freeze-up of the soil in autumn, and after spring thaw until September 1998. Tillage and residue treatments did not influence the recovery of autumn-applied or spring-applied Br. However, recovery of Br diminished with time: about 30% of the Br applied in autumn and 45% of that applied in spring remained in the soil profile by September 1998. Tillage, but not residue, treatments influenced the recovery of metribuzin. Recovery of metribuzin at the termination of this study was 6% or more in NT soil and 2% or less in CT and DO soil; greater recovery in NT soil was presumably a result of slower degradation in NT than in CT and DO. This study suggests that bromide (and thus nitrate) and metribuzin are more prone to leaching when applied in autumn and that tillage practices affect retention of metribuzin, but not nitrate, in the soil of Subarctic Alaska. Une utilisation prudente des engrais et des herbicides est cruciale au maintien ou à l’amélioration de la qualité de l’eau de surface et de l’eau souterraine dans les régions subarctiques, mais il existe peu de ...